Embracing nature's complexity: Immunoparasitology in the wild. (March 2021) - Mair, Iris; McNeilly, Tom N.; Corripio-Miyar, Yolanda; Forman, Ruth; Else, Kathryn J.
Graphical abstract: Highlights: Ecoimmunology allows the study of parasite immunity in the context of genetic and environmental variation. Studies in wild populations highlight the interactions between multiple variables. Poor availability of immunological tools has hampered progress in non-model species. Wild animal studies combine insights into host immunity and effects at population level. We propose a virtuous cycle of testing hypotheses in both lab and wild systems. Abstract: A wealth of research is dedicated to understanding how resistance against parasites is conferred and how parasite-driven pathology is regulated. This research is in part driven by the hope to better treatments for parasitic diseases of humans and livestock, and in part by immunologists who use parasitic infections as biomedical tools to evoke physiological immune responses. Much of the current mechanistic knowledge has been discovered in laboratory studies using model organisms, especially the laboratory mouse. However, wildlife are also hosts to a range of parasites. Through the study of host-parasite interactions in these non-laboratory systems we can gain a deeper understanding of parasite immunology in a more natural, complex environment. With a focus on helminth parasites, we here explore the insights gained into parasite-induced immune responses through (for immunologists) non-conventional experimental systems, and how current core findings from laboratory studies are reflected in these more natural conditions. The quality of the immune response is undoubtedly a central player in susceptibility versus resistance, as many laboratory studies have shown. Yet, in the wild, parasite infections tend to be chronic diseases. Whilst reading our review, we encourage the reader to consider the following questions which may (only) be answered by studying naturally occurring parasites in the wild: a) what type of immune responses are mounted against parasites in different hosts in the wild, and how do they vary within an individual over time, between individuals of the same species and between species? b) can we use wild or semi-wild study systems to understand the evolutionary drivers for tolerance versus resistance towards a parasite? c) what determines the ability of the host to cope with an infection and is there a link with the type of immune response mounted? d) can we modulate environmental factors to manipulate a wild animal's immune response to parasitic infections, with translation potential for humans, wildlife, and livestock? and e) in context of this special issue, what lessons for Type 2 immunity can we glean from studying animals in their natural environments? Further, we aim to integrate some of the knowledge gained in semi-wild and wild settings with knowledge gained from traditional laboratory-based research, and to raise awareness for the opportunities (and challenges) that come with integrating a multitude of naturally-occurring variables into immunoparasitological research.